2003
DOI: 10.1021/cm030393b
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide-Side-Chain Tethered Polyhedral Oligomeric Silsesquioxane Nanocomposites for Low-Dielectric Film Applications

Abstract: Low-dielectric-constant nanoporous films (dielectric constant, k = 2.4) with thermal integrity and controllable mechanical strength have been prepared by covalently tethering nanoporous polyhedral oligomeric silsesquioxane (POSS) molecules, 1-nm size, to the side chains of polyimide. The tethered POSS molecules in the amorphous polyimide retain a nanoporous crystal structure, but form an additional ordered architecture due to microphase separation. With this approach, the dielectric constant of the film can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
192
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(206 citation statements)
references
References 28 publications
13
192
0
1
Order By: Relevance
“…Verker et al [30] and Zhao and Schiraldi [31] attributed similar behaviour to a disruption of the polymer molecular (chain) structure brought on by POSS concentrations above 5 wt%. Liu and Zheng [32] suggested this observation is caused by a decrease in material density, due to an increase in nanocomposite porosity [33,34]. Additionally, the crosslinking densities per unit volume can decrease with increasing POSS content, compromising the reinforcement mechanism as a consequence.…”
Section: Thermomechanical Analysis 351 Stress-strain Analysismentioning
confidence: 99%
“…Verker et al [30] and Zhao and Schiraldi [31] attributed similar behaviour to a disruption of the polymer molecular (chain) structure brought on by POSS concentrations above 5 wt%. Liu and Zheng [32] suggested this observation is caused by a decrease in material density, due to an increase in nanocomposite porosity [33,34]. Additionally, the crosslinking densities per unit volume can decrease with increasing POSS content, compromising the reinforcement mechanism as a consequence.…”
Section: Thermomechanical Analysis 351 Stress-strain Analysismentioning
confidence: 99%
“…By this methodology, various ultra low-k PIs have been reported [10][11][12][13][14]. However, the attempts further reducing the k values of PIs below 1.5 seem to be more challenging because the conventional methods could only achieve a very limited air loading (<60%, volume ratio).…”
mentioning
confidence: 99%
“…It has nanometer-size cubic structure with wide surface area and controlled porosity, and can be functionalized with a wide variety of organic groups as monomer in a typical polymerization. Use of POSS derivatives as monomer has been demonstrated to be an efficient method in the design of nanocomposite materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] as well as in designing various hybrid polymers with POSS as side groups [16][17][18][19][20][21][22][23][24][25][26][27][28] or as chain end, [29][30][31] which exhibit desirable unique properties. Laine et al reported the synthesis of multi-functinal POSS as precursors of nanocomposite materials from commercially available typical silane-functionalized cubic silsesquioxane, octakis(dimethylsiloxy)octasilsesquioxane (Q 8 M 8 H ) by hydrosilylation.…”
mentioning
confidence: 99%